When the 'well-oiled machine' meets the 'pyramid of people:' Role perceptions and hybrid working practices of middle managers in a binational organization – ARTE. (December 2019) - Barmeyer, Christoph; Davoine, Eric; Stokes, Peter
This article examines the middle management representations of organization and managerial roles within a specific bicultural organizational context. The argument explores the extant cross-cultural management literature and identifies two predominant positions: a functionalist-stable stance and a dynamically interpretive perspective of culture. Historically, both positions have contributed to understanding management roles and behaviours in different cross-cultural contexts; however, each also possesses limitations. In response, the argument elaborates a multi-paradigmatic model and framework that synergise elements of the respective approaches. An interpretive methodology using a distinctive qualitative case study of the Franco-German collaborative media venture ARTE is developed. The researchers conducted 31 interviews with French and German ARTE middle managers in order to determine their perceptions of middle-manager roles in this context. The article identified differences in managerial role perceptions and behaviours as well as hybrid working practices as a result of intercultural adaptation and learning in addition to implications, limitations and future directions in the study.